Karakteristik Pembakaran Biomassa Sawit sebagai Alternatif Penghasil Energi Panas dengan Menggunakan Fluidized Bed Combustor - Mahidin Mahidin; Hisbullah Hisbullah; Oktari Taka; Muhammad Irsyadul Afkar (Jurnal Inovasi Ramah Lingkungan, 2022)
One of the technology that can be utilized to meet the energy demands is biomass combustion. In this study, the biomass sources is from part of the palm oil such as empty fruit bunches, palm oil fiber, palm oil fronds, and palm oil shell. This research was conducted using a fluidized bed combustor (FBC) tool, which aims to observe the characteristics of the combustion process on FBC devices. The characteristics observed in this study were the combustion temperature profile, flue gas composition, and the composition of the ash deposit chemical compound. The results obtained from this study are the best combustion temperature profile which is in the condition of combustion of 2 kg biomass with 1,25 m /minute velocity of air and the maximum combustion temperature obtained in the condition of combustion with a mass of 3 kg biomass with 1,25 m 3 /minute velocity of air. The best combustion conditions occur when the ammount of biomass is 3 kg and with 1,25 m 3 /minute velocity of air with the least amount of O2 and the highest amount of CO2 respectively 0.2 % and 19.9 %. The highest combustion efficiency in the FBC device is when burning 1 kg of biomass with 0,625 m 3 /minute velocity of air in the 4th minute which is equal to 94.9%. 3